MiR-2779-x, a key microRNA that is related to the tumorigenicity of the MDCK cell line - Yang, Di; Huang, Lingwei; Shi, Jiachen; Liu, Zhenbin; Wang, Jiamin; Ma, Zhongren; Abudureyimu, Ayimuguli; Qiao, Zilin; Chen, Jianguo (Biochimica et biophysica acta. General subjects, 2025)
The tumorigenicity of MDCK cell line is a major concern with respect to its safety for vaccine production, the effect of miRNAs on the tumorigenicity of MDCK cells is poorly understood. In this study, we performed miRNA-Seq on two MDCK cell lines with tumorigenic potential and their derived monoclonal cell lines that lack tumorigenicity. Through bioinformatics analysis, we identified differentially expressed miRNAs and conducted GO and KEGG pathway analyses of their target genes. Our results indicated that miR-2779-x and its target genes exhibited the most significant characteristics associated with tumorigenesis. Injection of live cells overexpressing miR-2779-x into nude mice resulted in a markedly reduced tumorigenesis rate (1/10). Overexpression of miR-2779-x significantly decreased the proliferation and migration capabilities of MDCK cells while enhancing their invasive potential. To identify and localize miR-2779-x target genes, we employed bioinformatics prediction, RT-qPCR, immunofluorescence assays (IFA), fluorescence in situ hybridization (FISH), and dual-luciferase reporter assays. We found that miR-2779-x negatively regulates the expression of PI3KR1 and Caspase 9 at both the gene and protein levels. Additionally, miR-2779-x co-localizes with PI3KR1 in the cytoplasm and directly targets the 3’UTR of PI3KR1. Overexpression of PI3KR1 in miR-2779-x-overexpressing cells restored cellular functions, leading to increased proliferation and migration but decreased invasion. Moreover, miR-2779-x modulates MDCK cell growth and tumorigenesis by influencing the expression and phosphorylation levels of proteins involved in the PI3K/AKT and apoptosis signaling pathways. We proposed the key pathways of miRNA involvement in MDCK cell tumorigenicity and initially revealed the function of miR-2779-x in MDCK cell tumorigenicity. •MiR-2779-x could reduce tumorigenic potential, inhibit cell proliferation and migration, while enhancing cell invasiveness.•MiR-2779-x directly binds to the 3’UTR of PI3KR1, thereby negatively regulating its expression.•MiR-2779-x regulated the tumorigenic of MDCK cells by the PI3K/AKT signaling pathway and apoptosis signaling pathway.